GDF15 orchestrates mitochondrial-immune crosstalk via SMAD7-HIF-1α-PKM2 cascade to attenuate septic liver injury - Kuang, Xiandong; Niu, Zhili; Liu, Wenqiang; Huang, Zhaoyang; Li, Shuo; Zhang, Ye; Wang, Li; Cai, Xin; Wang, Faxi; Zhang, Pingan (Frontiers in Immunology, 2026)
BackgroundSepsis-induced multi-organ failure involves pathological crosstalk between mitochondrial dysfunction and hyperinflammation, yet endogenous protective mechanisms remain incompletely defined. This study investigates Growth Differentiation Factor 15 (GDF15) as a potential regulator of sepsis tolerance.MethodsUsing LPS-challenged mouse endotoxemia and a murine macrophage (RAW264.7) cell line model, we assessed GDF15’s functional role through: (1) recombinant Adeno-Associated Virus serotype 8 (rAAV8)-mediated tissue-specific overexpression, (2) siRNA knockdown, (3) pharmacological modulation (BAY 87-2243/Hypoxia-Inducible Factor 1-alpha (HIF-1α) inhibitor, Shikonin/PKM2 inhibitor, Asiaticoside/SMAD7 activator), and (4) comprehensive metabolic-inflammatory phenotyping including mitochondrial complex integrity (assessed via UQCRC1, Ubiquinol-Cytochrome c Reductase Core Protein 1), cytokine dynamics (TNF-α, IL-6) and lactate metabolism.ResultsLPS challenge induced time-dependent mitochondrial dysfunction concurrent with cytokine storms and compensatory GDF15 upregulation in both liver and macrophages. Hepatocyte-specific GDF15 overexpression attenuated injury through restored mitochondrial integrity, diminished macrophage infiltration, and reduced systemic inflammation, as evidenced by significantly lower levels of circulating TNF-α and IL-6. Mechanistically, GDF15 preserved mitochondrial homeostasis by inducing SMAD7 expression while suppressing HIF-1α accumulation and PKM2 nuclear translocation. Pharmacological HIF-1α/PKM2 inhibition recapitulated GDF15’s protective effects, restoring mitochondrial function and reducing inflammation even in GDF15-deficient models. Clinical analysis of a sepsis patient cohort (n=119) confirmed a significant elevation of circulating GDF15, with its levels strongly correlating with disease severity scores. Critically, SMAD7 activation attenuated HIF-1α accumulation and rescued mitochondrial failure independently of GDF15 status.ConclusionGDF15 orchestrates sepsis tolerance through the SMAD7-HIF-1α axis, preserving mitochondrial integrity while resolving metabolic-inflammatory dysregulation, notably by suppressing the release of pro-inflammatory cytokines such as TNF-α and IL-6. This study identifies GDF15 as a central guardian of mitochondrial-immune homeostasis in sepsis, positioning it as both a robust severity biomarker and a promising therapeutic target for mitochondrial resuscitation.